Chitons of the genus Lepidochitona (Mollusca: Polyplacophora) in the Indian Ocean and ordering of species compositions of some genera of the subfamily Tonicellinae - Sirenko, Boris (Zootaxa, 2023)
The species composition of the genus Lepidochitona in the Indian Ocean and Southeast Atlantic is reviewed. To the so far known three species of this region, two new species are added. One of them, L. africana n. sp., inhabits the area from False Bay on the southern coast of South Africa to Mpenjati, KwaZulu-Natal. The second species, L. pakistana n. sp., is restricted to the shallow waters of Pakistan. In addition, the previously considered rare species L. turtoni is revisited. Lastly, the controversial issues of the taxonomy and composition of the genera Lepidochitona and Cyanoplax, are discussed.